ANALISIS KESEHATAN BANK DENGAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL PADA BANK MILIK NEGARA TAHUN 2013-2017 - Skalis Winda Munte; Selmi Dedi; Ted Matheus Suruan (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
This research was aimed to analysis risk base bank rating using RGEC (Risk Profile, Good Corporate Governance, Earning, and Capital ) method in Bank of Public Company 2013-2017. This research was a comparative research. The analyzer was used in this research is RGEC method. Risk Profile was assessed by, credit risk, market risk, and liquidity risk. Good Corporate Governance was assessed by self assessment of bank report. Earning was assessed by, i.e ROA, ROE, NIM, and BOPO. And for capital was assessed by CAR. The results of the study that PT. Bank Rakyat Indonesia (Persero) Tbk obtains the highest average weighted Composite Rating, which is 94.67%., PT. Bank Negara Indonesia (Persero) Tbk came in second place at 87.11%. and PT. Bank Tabungan Negara (Persero) Tbk obtains the lowest weighted Composite Rating weight of 85.78%. However, overall the three State-Owned Banks are still rated very healthy. However, it is hoped that further researchers will be able to take on more banks to provide a broader picture.